Validity of the Development of Problem Solving Oriented Electronic Booklet Teaching Materials for Class V Students - Nikmawati, Surga; Nurlina, Nurlina; Ma'ruf, Ma'ruf; Rahmawati, Rahmawati; Imran, Muh Erwinto (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2024)
This research aims to increase the validity of problem solving-oriented electronic booklet (e-booklet) teaching materials in fifth grade science learning in elementary schools. The type of research is development research using the ADDIE model which consists of analysis, design, development, implementation and evaluation stages. The subjects in this research were 25 class V students. The instruments used were material and media expert validation sheets. Data analysis techniques were carried out to see the level of validity of problem-solving oriented electronic booklet (e-booklet) teaching materials. Based on data analysis of filling out expert test instruments, it shows that the media and material validation sheets are declared feasible or valid with a validity level of 1 which is in the very high criteria.